Diel variation of fish community in sandy beaches of southeastern Brazil (Brazilian Journal of Oceanography, 2008)
Fish living in coastal waters present behavior patterns ruled by environmental light levels. Diel variations in fish community structure were investigated at Arraial do Cabo surf zone (22º58'S, 42º01'W). From September/2001 to August/2002 monthly sampling consisted of 12 hauls of a beach seine during the day and at night at Praia dos Anjos, Praia Grande and Prainha beaches. Different temporal distribution patterns of the ichthyc community were recorded. At Praia dos Anjos, total richness was higher at night while the average number of species, CPUE, Margalef's richness and Shannon diversity were generally higher during the day. We believe that this pattern was caused by the displacement of some species such as Harengula clupeola,Trachinotus carolinus and Umbrina coroides at night to deeper areas searching for food or for predator avoidance. At Praia Grande and Prainha the average number of species, CPUE, richness and diversity indexes were generally higher at night with the dominant species H. clupeola, Pomatomus saltatrix and Sardinella brasiliensis. It is suggested that the main factor to diel variation is the protection against predators due to darkness, making visualization of the prey difficult, besides the presence of seasonal macroalgae beds at Prainha, which might function as a food area for piscivorous fishes due to the proximity of larger individuals in shallower water especially at night.